\(x^2+2+x-2=-8\)
\(\Leftrightarrow x^2+x+8=0\)
Ta có: \(x^2+x+8=x^2+2.\dfrac{1}{2}.x+\left(\dfrac{1}{2}\right)^2-\left(\dfrac{1}{2}\right)^2+8=\left(x+\dfrac{1}{2}\right)^2+\dfrac{31}{4}\ge\dfrac{31}{4}>0\)
--> pt vô nghiệm
\(x^2+2+x-2=-8\)
\(\Leftrightarrow x^2+x+8=0\)
Ta có: \(x^2+x+8=x^2+2.\dfrac{1}{2}.x+\left(\dfrac{1}{2}\right)^2-\left(\dfrac{1}{2}\right)^2+8=\left(x+\dfrac{1}{2}\right)^2+\dfrac{31}{4}\ge\dfrac{31}{4}>0\)
--> pt vô nghiệm
giải phương trình chứa ẩn ở mẫu:
1) x+6/x-5 + x-5/x+6 = 2x^2+23x+61/x^2+x-30
2) 6/x-5 + x+2/x-8 = 18/(x-5)(8-x) - 1
3) x^2-x/x+3 - x^2/x-3 = 7x^2 - 3x/9-x^2
Giải các phương trình:
a) \(\dfrac{1}{x-2}\) + 3 = \(\dfrac{3-x}{x-2}\)
b) \(\dfrac{8-x}{x-7}\) - 8 = \(\dfrac{1}{x-7}\)
c) \(\dfrac{1}{x-1}\) + \(\dfrac{2x}{x^2+x+1}\) = \(\dfrac{3x^2}{x^3-1}\)
d) \(\dfrac{y+5}{y^2-5y}\) - \(\dfrac{y-5}{2y^2+10y}\) = \(\dfrac{y+25}{2y^2-50}\)
giải phương trình sau
a) 90/x-36/x-6=2
b)x=3/x-3-1/x=3/x(x-3)
c)3/x+2-2/x-2+8/x^2-4=0
d)5/x+7+8/2x+14=3/2
Giải các phương trình sau:
a) \(\dfrac{7x-3}{x-1}=\dfrac{2}{3}\).
b) \(\dfrac{2\left(3-7x\right)}{1+x}=\dfrac{1}{2}\).
c) \(\dfrac{1}{x-2}+3=\dfrac{3-x}{x-2}\).
d) \(\dfrac{8-x}{x-7}-8=\dfrac{1}{x-7}\).
1. Giải phương trình
a) \(\frac{2}{x^2-x-6}+\frac{x+1}{x^2+x-12}=\frac{x}{x^2+6x+8}\)
b) \(\frac{2x-5}{x^2+5x-36}-\frac{x-6}{x^2+3x-28}=\frac{x+8}{x^2+16x+63}\)
c) \(\frac{x-2}{4x^2-29x+30}-\frac{x+1}{20x^2-13x-15}=\frac{x+2}{5x^2-274x+18}\)
Giúp mk nha
Giải các phương trình
1/ \(\dfrac{1}{x^2+3x+2}+\dfrac{1}{x^2+5x+6}+\dfrac{1}{x^2+7x+12}=\dfrac{1}{6}\)
2/ \(\dfrac{1}{x^2-6x+8}+\dfrac{1}{x^2-10x+24}+\dfrac{1}{x^2-14x+48}=\dfrac{1}{9}\)
3/ \(\dfrac{1}{x^2-3x+3}+\dfrac{2}{x^2-3x+4}=\dfrac{6}{x^2-3x+5}\)
4/ \(\dfrac{6}{\left(x+1\right)\left(x+2\right)}+\dfrac{8}{\left(x-1\right)\left(x+4\right)}=1\)
5/ \(4\left(x^3+\dfrac{1}{x^3}\right)=13\left(x+\dfrac{1}{x}\right)\)
6/ \(\dfrac{4x}{4x^2-8x+7}+\dfrac{3x}{4x^2-10x+7}=1\)
7/ \(\dfrac{x^2-3x+5}{x^2-4x+5}-\dfrac{x^2-5x+5}{x^2-6x+5}=-\dfrac{1}{4}\)
8/ \(x.\dfrac{8-x}{x-1}\left(x-\dfrac{8-x}{x-1}\right)=15\)
\(\dfrac{2}{-x^2+6x-8}-\dfrac{x-1}{x-2}=\dfrac{x+3}{x-4}\)
Giải các phương trình sau:
a) \(x^3-x^2-\dfrac{8}{x^3-x^2}=2\)
b) \(\dfrac{x^4}{2x^2+1}+\dfrac{2x^1+1}{x^4}=2\)
c) \(x\left(\dfrac{8-x}{x-1}\right)\left(x-\dfrac{8-x}{x-1}\right)=15\)